Middle manager involvement and corporate culture in the strategic planning practices: The Indonesian corporation evidence - Ridwan, M. Sihab; S, Sumiati; AB, Fausta; P, Sunu; Henrycus, Henrycus (Edelweiss Applied Science and Technology, 2025)
This study looks at how managers are involved in the strategic planning process and how goals and budgets are related. This study also examines how effective strategic planning techniques are supported by company culture. To gather data for this study, a multiple case study was employed. In-depth semi-structured and unstructured interviews with planning members serving as key informants in each chosen firm were used as the data collection method. The selection of the six companies was based on their strong performance. Important findings from this study include the recognition of the link between goals and budgets, the proof of the crucial role manager commitment plays in strategy development and implementation, and other related findings. The study’s overall findings offered insightful information about the role that organizational culture plays in supporting successful planning techniques, as well as the role that manager commitment, company goals, and budget linkage play.